Kiai charismatic leadership in improving the quality of education at Mamba'ul Ulum Islamic Boarding School in Jember - Faruq, Muhammad; Al haj, Zainuddin; Tsauri, Sofyan (Jurnal Akuntabilitas Manajemen Pendidikan, 2023)
Engaging leadership is the result of attribution theory. According to this theory, followers attribute noble or exceptional leadership qualities to their leaders when they witness them engaging in engaging leadership behaviors. This study utilized a qualitative methodology with a detailed qualitative research design. Subjects were identified using strategic methods. Information collection methods involving observation, interview, and written notes. Milles and Huberman's dynamic paradigm for data analysis consisting of data compression, data display, and findings. Triangulation of data sources and methods was used to verify reliability. The following conclusions can be made based on the research findings: Kiai's method in leading better teaching at Mamba'ul Ulum 1. Kiai Pondok Pesantren Dukuh Mincek practices a democratic form of leadership in which he delegates authority to administrators and ustaz in carrying out activities and through general supervision, as well as regularly conducting musyawarah with alumni and his brothers on matters relating to school development. 2. Efforts made by Kiai to improve Education Standards at Pondok Pesantren Mamba'ul Ulum include: recitation of the yellow book, reading maulid diba', khitobah alfiah ibnu malik, business and familiarizing tahajut rituals.